Forecasting of the main indicators of the development of the Russian economy for the period up to 2033 according to Rosstat data for 2002-2023 using the delayed regression method ("Journal "U". Economy. Management. Finance.", 2024)
According to Rosstat data for 2002-2023 on the dynamics of gross output, value added, fixed assets, number and salary for financial activities of the Russian Federation, forecasts were made for 3 types of regression (autoregression, reflexive regression, multiple reflexive regression). As a result, the most plausible forecast scenarios up to 2028 were obtained, which allowed us to draw a general conclusion about the prospects for development.
Keywords: regression; regression with shifted factors; mirror regression; correlation; coefficient of determination; multiple regression; forecast; trend; financial activity; economics